About transport of dispersed particles by a two-phase filtration flow - Nikiforov, Anatoliy Ivanovich; Sadovnikov, Roman Valerievich; Nikiforov, Grigoriy Anatolievich (Computational Continuum Mechanics, 2013)
A new mathematical model is proposed to describe the transport of dispersed particles by a two-phase filtration flow. Particle deposition in a porous body and particle detachment from pore walls are taken into account. A numerical solution is obtained by the control volume method. It is shown that the majority of solid particles are washed away from an oil reservoir by the water flow. The effect of redistribution of solid particles in the pore channels of various sizes is revealed.
Keywords: filtration; dispersed particles; colmatation; suffosion; control volume method